New records of postglacial walrus and a review of Quaternary marine mammals in New Brunswick - Miller, Randall (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
New records for postglacial walrus, Odobenus rosmarus, from New Brunswick raise the number of documented specimens in the province to nine. One of the previous reports was a tusk fragment, one was a partial cranium, one was an almost complete skeleton. Sixnew specimens arerepresentedbypartial or complete skulls. ThreearefromoldercollectionsoftheNew Brunswick Museum. Two of the most recent finds were dredged from the Bay of Fundy. Walrus form part of a small Quaternary marine mammal fauna in New Brunswick. Three species of whale, beluga, narwhal and minke (?), as well as harp (?) seal and walrus, have been reported over the past century. However, only walrus and narwhal can be confirmed by existing specimens. Marine mammal fossils from Quaternary deposits in New Brunswick demonstrate environmental requirements compatible with summer sea-surface temperatures postulated from earlier studies of littoral invertebrates. Radiocarbon dates associated with some of the marine mammals suggest they inhabited New Brunswick's coastal waters by at least 12,500 years B.P.